PCSK9 Inhibition: From Current Advances to Evolving Future - Liu, Chunping; Chen, Jing; Chen, Huiqi; Zhang, Tong; He, Dongyue; Luo, Qiyuan; Chi, Jiaxin; Hong, Zebin; Liao, Yizhong; Zhang, Shihui; Wu, Qizhe; Cen, Huan; et al. (Cells (Basel, Switzerland), 2022)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secretory serine protease synthesized primarily by the liver. It mainly promotes the degradation of low-density lipoprotein receptor (LDL-R) by binding LDL-R, reducing low-density lipoprotein cholesterol (LDL-C) clearance. In addition to regulating LDL-R, PCSK9 inhibitors can also bind Toll-like receptors (TLRs), scavenger receptor B (SR-B/CD36), low-density lipoprotein receptor-related protein 1 (LRP1), apolipoprotein E receptor-2 (ApoER2) and very-low-density lipoprotein receptor (VLDL-R) reducing the lipoprotein concentration and slowing thrombosis. In addition to cardiovascular diseases, PCSK9 is also used in pancreatic cancer, sepsis, and Parkinson’s disease. Currently marketed PCSK9 inhibitors include alirocumab, evolocumab, and inclisiran, as well as small molecules, nucleic acid drugs, and vaccines under development. This review systematically summarized the application, preclinical studies, safety, mechanism of action, and latest research progress of PCSK9 inhibitors, aiming to provide ideas for the drug research and development and the clinical application of PCSK9 in cardiovascular diseases and expand its application in other diseases.